Gidenlerin ardından: Şeyhî ve Ahmet Paşa’nın "Sen Gideli” redifli gazelleri üzerine bir karşılaştırma - Karaman, Gülay; Karaman, Gülay (Turkish Studies, 2013)
En az iki varlık ya da kavram arasında benzer ve farklı yönlerini bulmak amacıyla karşılaştırmalar yapmak insan aklı ve düşüncesinin en önemli özelliklerinden biridir. Bilimsel bir yöntem olarak karşılaştırma ise bütün bilim dalları için son derece önem taşır. Karşılaştırmalı edebiyat; edebî ürünleri inceleyen, araştıran ve eleştiren genel edebiyat biliminin bir alt dalıdır. Karşılaştırmalı edebiyatın asıl işlevi farklı dillerde yazılmış en az iki edebî ürünü karşılaştırma yöntemiyle incelemektir. Bununla beraber, incelenen eserler aynı dilde yazılmış olabileceği gibi aynı sanatçının iki ayrı eseri de incelemeye konu olabilir. Şeyhî ve Ahmet Paşa’nın “sen gideli” redifli gazelleri üzerine yaptığımız çalışma klasik Türk edebiyatı alanında bir karşılaştırmalı edebiyat çalışmasıdır. Esasen klasik Türk edebiyatı, İslâm edebiyatı özellikle de Arap ve Fars edebiyatları ile yakın ilişkiler içerisinde olduğu için karşılaştırmalı edebiyat için çok uygun bir alandır. Klasik Türk şiiri hem içerik hem de şekil yönünden önceden hazır temel bir malzemeye dayanır. Redif, önceden hazır olan bu temel malzemelerden biridir. Klasik Türk şiirinde redif şekilsel bir özellik, ahengi sağlayan bir unsur olmanın ötesinde şaire verdiği ilhamlarla şiirin anlamını konu etrafında toplayan bir mihver olarak görülmüştür. Ayrılık acısı ve hasretin en yoğun biçimde ifade edildiği şiirlerin başında “sen gideli” redifli gazeller gelir, denilebilir. Bu çalışma için taradığımız yüze yakın divandan edindiğimiz sonuca göre “sen gideli” redifi, 15. yy. klasik Türk şiirinde bayağı rağbet görmüştür. Araştırmamıza göre 15. yy. şairi Şeyhî “sen gideli” redifini kullanan ilk şairdir. Şeyhî’yi diğer 15. yy. şairleri Ahmet Paşa, Karamanlı Nizâmî, Karamanlı Aynî ve Mihrî Hatun takip eder. Fakat “sen gideli”, 15. yy.dan önce “Beyrek gideli” ve “sen gideli” ifadeleriyle Dede Korkut Hikâyeleri’nde Kam Büre Bey-Oğlu Bamsı Beyrek Boyu adlı hikâyede kullanılmıştır. Bu makale 15. yy. şairlerinden Şeyhî ve Ahmet Paşa’ya ait “sen gideli” redifiyle yazılmış iki gazeli karşılaştırmayı amaçlamaktadır. Şeyhî’nin gazeli “sen gideli” redifiyle yazılmış ilk şiir olması bakımından önemlidir. Diğer taraftan Ahmet Paşa’nın gazelinin önemi diğer 15. yy. şairlerini etkileme gücünden gelir. Bu iki gazel şekil ve muhteva açısından karşılaştırılacaktır.

To make comparisons in order to find similarities and different aspects between at least two assets or concepts is one of the most important properties of human mind and idea. Also as a scientific method, comparison is extremely important for every branch of science. Comparative literature is a sub-branch of the science and letters which examines, researches and criticizes the products of the literature. The main function of comparative literature is to examine at least two different literary products that are written in different languages by the method of comparison. However, works examined can be written in the same language or two different works by the same author/poet also may be subject to scrutiny. Our study over the ghazels of Şeyhî and Ahmet Paşa with the redif “since you have gone” is a comparative literature study in the area of classical Turkish literature. In fact, since classical Turkish literature has close relations with Islamic literature, especially Arab and Persian literature, it is a very convenient area for comparative literature. In terms of both content and form classical Turkish poetry is based on a basic pre-prepared material. Redif is one of these basic pre-prepared materials. In classical Turkish poetry redif is not only a formal feature, an element of harmony but also it has been seen as a pivot since it collects the meaning of the poem around the subject by inspring the poet. It can be said that the most intense pain of seperation and longing is expressed in the poems with the redif “since you have gone”. After scanning about a hundred of divans for this study, it is found out that the redif “since you have gone” had been very famous among 15th century classical Turkish poetry. According to our research, a 15th century poet Şeyhî was the first one in using the redif “since you have gone”. Şeyhî was followed by the other 15th century poets Ahmet Paşa, Karamanlı Nizâmî, Karamanlı Aynî and Mihrî Hatun. But earlier than 15th century “since you have gone” was used in the story called Kam Büre Bey-Oğlu Bamsı Beyrek Boyu in Dede Korkut Hikâyeleri with the expression of “since Beyrek has gone” and “since you have gone”. This article aimes to compare two ghazels with the redif “since you have gone” by the 15th century poets Şeyhî and Ahmet Paşa. Şeyhî’s ghazel is important since it is the first poem written with the redif “since you have gone”. On the other hand the importance of the ghazel of Ahmet Paşa comes from its power of influencing the other 15th century poets. These two ghazels will be compared in terms of form and content.
After the ones who have gone: A comparison over the ghazels of Şeyhî and Ahmet Paşa with the redif “since you have gone”
Keywords: Karşılaştırmalı edebiyat, klasik Türk şiiri, redif, “sen gideli”, gazel, Şeyhî, Ahmet Paşa.; Comparative literature, classical Turkish poetry, redif, “since you have gone”, ghazel, Şeyhî, Ahmet Paşa.; Karşılaştırmalı edebiyat; Klasik Türk şiiri; Redif; Gazel; Şeyhî; Ahmet Paşa; Sen gideli; Comparative literature; Classical Turkish poetry; Since you have gone; Ghazel